Associations between indoor environment and lifestyles and sick building syndrome symptoms among adults in Taiyuan and Urumqi of China. (19th July 2022) - Fu, Pengfei; Zhao, Zhuohui; Norback, Dan; Zhang, Xin; Yung, Ken Kin Lam
Abstract: The complex and uncertain causes of sick building syndrome (SBS) have become one of the most challenging and hot issues worldwide. Studies on the correlation between indoor environment and SBS based on local characteristics are relatively limited in China. We studied typical SBS risk factors related to the indoor environment and lifestyle in two northern Chinese cities. The study population was drawn from parents of pre‐school children in randomized daycare centers in Taiyuan, Shanxi, and Urumqi, Xinjiang, China ( N = 6838). Data on SBS and indoor environment were obtained from cross‐sectional questionnaires. Odds ratios (OR) were estimated by multilevel logistic regression and adjusted using gender, atopy, own smoking, home size, and dampness index. Results showed that location, homeownership, year of construction completion, changes in the indoor environment (new furniture and decorations), and changes in indoor air (smoking, burning mosquito repellent and incense, cooking fuels including electricity, natural gas, coal, and wood) might contribute to different levels of SBS in Chinese adults, including eye, nasal, throat, dermal symptoms, and headache and tiredness. The results of the subgroup analysis suggest city and gender differences in susceptibility. Daily cleaning, window opening, and improved ventilation effectively improved SBS. People should improve their indoor environment and lifestyles based on sensitivity factors, gender, and geographic characteristics to reduce SBS risks.